Describing Phraseological Devices in Medical Abstracts: An English/Spanish Contrastive Analysis - López-Arroyo, Belén; Méndez-Cendón, Beatriz (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2007)
AbstractGenre studies have been mainly focused on the rhetorical structure of research papers. However, genre theorists have not systematically studied either relationships among related genres or interlingual studies between genres. The present study aims at describing and comparing the rhetorical and phraseological structures of abstracts in English and Spanish in order to observe how information is rendered in the two languages under analysis. Our methodology is descriptively performed on a comparable corpus of abstracts in the field of diagnostic imaging and published in well-reputed journals. We will determine composition strategies by means of a semantic and functional approach so as to establish their similarities and differences in this genre. Our results will be primarily of help to translators, technical writers and ESP students to better understand some of the discourse aspects of rendering scientific information in both languages.